A Different Kind of Rigor: What Climate Scientists Can Learn from Emergency Room Doctors. Issue 2 (4th May 2018) - Peacock, Kent A.
ABSTRACT: James Hansen and others have argued that climate scientists are often reluctant to speak out about extreme outcomes of anthropogenic carbonization. According to Hansen, such reticence lessens the chance of effective responses to these threats. With the collapse of the West Antarctic Ice Sheet (WAIS) as a case study, reasons for scientific reticence are reviewed. The challenges faced by scientists in finding the right balance between reticence and speaking out are both ethical and methodological. Scientists need a framework within which to find this balance. Such a framework can be found in the long-established practices of professional ethics.